Retoryka ciągłości: o dziedzictwie prawnym II Rzeczypospolitej i rządów komunistycznych - Kozerska, Ewa; Scheffler, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The aim of the article is to establish whether the continuity between the Second and Third Polish Republics officially declared by the Polish elites is based on facts. The authors analyse the question with regard to three areas: symbolic events handing over of the presidential insignia in 1990 and the 1998 resolution of the Senate of the Republic of Poland on legal continuity, judgements of ordinary courts and the Constitutional Court as well as legal scholarship. In their conclusion they point out that the rhetoric of continuity between the Second and the Third Polish Republics on the legal level hides real continuity between the communist regime and the normative system in force in Poland since 1989.
Keywords: prawo; totalitaryzm; ciągłość; zmiana; praworządność; formy symboliczne